Perspectives on Sleep from Multiethnic Community Parents, Pediatric Providers, and Childcare Providers. Issue 7 (September 2020) - Sadler, Lois S.; Banasiak, Nancy; Canapari, Craig; Crowley, Angela A.; Fenick, Ada; O'Connell, Meghan; Ordway, Monica R.; Sude, Leslie; Trevino, Sandra; Redeker, Nancy S.
Abstract: Objective: To describe the perceptions of (1) parents, childcare, and health care providers regarding sleep health among multiethnic infants and toddlers living with socioeconomic adversity, (2) factors that contribute to sleep health and its consequences, and (3) best ways to promote sleep health in these children. Methods: Nested within a larger community-engaged mixed methods study, we used a descriptive qualitative design to describe the experience of multiethnic young parents who were raising 6- to 36-month-old children, pediatric health care providers, and childcare providers living and working in an urban under-resourced community. Semistructured interviews with 25 parents and 16 providers were conducted, transcribed, coded, and analyzed using thematic analysis by a 6-member research team. Interviews continued until themes were saturated. Results: Parent responses and provider responses resulted in overlapping and divergent findings. Common themes among all respondents were the importance of sleep, interest and desire for more sleep health information, and common environmental/social impediments to healthy family sleep. Divergent themes included the importance of bedtime routines and timing, views on the family bed, importance of naps, and healthy sleep aids. Childcare centers were suggested as good sites for sleep health promotion programs. Conclusion: Sleep is a topic of interest and importance for young families. There are unique family challenges to be considered in any sleep health promotion program tailored to the needs of the community. The voices of parents and community providers are valuable assets informing the development of novel family-friendly approaches for decreasing sleep disparities and improving the health of young children and families. Abstract : This article has supplementary material on the web site: www.jdbp.org.